Eight-handed Vishnu - 042 - Saurabh Saxena (2022)
Image courtesy : Saurabh Saxena - https://puratattva.in/ The hands of the deity are holding artifacts pertaining to both Vishnu and Shiva. Of Vishnu, there is the conch and the discus and of Shiva there is the drum and noose. Additionally, one of the artifacts in hand is a Japamala - the prayer beads.